2016
DOI: 10.1519/jsc.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Power Qualities Are Highly Associated With Punching Impact in Elite Amateur Boxers

Abstract: This study investigated the relationship between punching impact and selected strength and power variables in 15 amateur boxers from the Brazilian National Team (9 men and 6 women). Punching impact was assessed in the following conditions: 3 jabs starting from the standardized position, 3 crosses starting from the standardized position, 3 jabs starting from a self-selected position, and 3 crosses starting from a self-selected position. For punching tests, a force platform (1.02 × 0.76 m) covered by a body shie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
142
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(180 citation statements)
references
References 31 publications
11
142
2
12
Order By: Relevance
“…In combat sports, jumping performance can explain approximately 75% of the variance in punching forces, highlighting the importance of legs' contribution in the explosive extension of the arm to the target (12). The results of the present study expand our knowledge from previous fencing studies of Tsolakis and vagenas (25) and Turner et al (28), giving important information to coaches of a large number of different strength abilities to be trained so as to build the optimal neuromuscular profile for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In combat sports, jumping performance can explain approximately 75% of the variance in punching forces, highlighting the importance of legs' contribution in the explosive extension of the arm to the target (12). The results of the present study expand our knowledge from previous fencing studies of Tsolakis and vagenas (25) and Turner et al (28), giving important information to coaches of a large number of different strength abilities to be trained so as to build the optimal neuromuscular profile for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Inúmeros trabalhos foram desenvolvidos sobre esta temática, especialmente nas duas últimas décadas, com destaque para investigações sobre a estrutura temporal e fatores discriminantes de desempenho no boxe [90][91][92] , na esgrima 93 , no judô [94][95][96][97][98][99] , no karatê [100][101][102] , na luta olímpica 103 e no taekwondo 104 . Além destas potenciais aplicações, o conhecimento gerado a partir da análise técnica, tática e de estrutura temporal, juntamente com aquele oriundo de investigações sobre a demanda energética da luta, tem permitido a elaboração de processos de avaliação mais especí cos. Neste contexto, vale destacar o processo de avaliação física de atletas do boxe 105 , da esgrima 106 , do judô [107][108] -incluindo atletas paralímpicos 109 , do karatê [110][111][112][113][114] e do taekwondo [115][116] , com utilização de testes especí cos -inclusive com a elaboração de tabelas classi catórias [117][118] e análise discriminante entre diferentes testes 119 e/ou em situações especí cas das diferentes modalidades [120][121][122] . A compreensão de como treinam os atletas que participaram dos Jogos Olímpicos 123 , de quais competições participam durante o processo de quali cação para esta, com determinação da importância relativa quanto ao posicionamento em "rankings" internacionais [124][125][126] e do intervalo ideal entre estas competições para a maximização do desemp...…”
Section: Treinamento Em Modalidades Esportivas De Combateunclassified
“…Accordingly, Sanchez-Medina et al (2010) demonstrated that the mechanical values collected during the propulsive phase of a lift better reflected the differences in neuromuscular performance between two given individuals. In fact, JS MPP has been shown to be highly correlated with specific performance in athletes from distinct sports (Loturco et al, 2014, 2015a, 2016a). Additionally, it has been shown that training at the optimum load produces greater performance improvements than traditional strength training and reduces the speed-power decrements that usually occur during soccer preseasons (Loturco et al, 2015d, 2016b).…”
Section: Introductionmentioning
confidence: 99%